Wildfires in the Siberian Arctic - Viacheslav I. Kharuk; Maria L. Dvinskaya; Sergei T. Im; Alexei S. Golyukov; Kevin T. Smith (Fire, 2022)
Wildfires are increasingly understood as an ecological driver within the entire Arctic biome. Arctic soils naturally store large quantities of C, as peat has formed throughout the Holocene. For the Siberian Arctic, we used observations from the MODIS remote sensing instrument to document changes in frequency, geographic extent, and seasonal timing of wildfires as well as vegetation productivity (GPP, NPP, EVI). We also used correlation and regression analysis to identify environmental factors of temperature, precipitation, and lightning occurrence associated with these changes. For the Siberian Arctic as a whole, we found that the decadal frequency of wildfire tripled from the 2001–2010 to the 2011–2020 periods. Increased decadal frequency was accompanied by the increased extent of the burnt area by a factor of 2.6. This increase in fire frequency and extent was not uniform, with the greatest increase in western Siberia with no marked increase for the Siberian Far East. These changes were accompanied by the northward migration of the northern limit of wildfire occurrence and an increase in duration of the wildfire season. We found that annual fire frequency and the extent of burnt areas were related to various combinations of seasonal air temperature, precipitation, ground moisture, and lightning frequency. After fires, vegetation productivity rapidly recovered to pre-fire levels. The northward spread of wildfire into the tundra will release carbon long-stored as peat. The enhanced vegetation productivity, rapid recovery of carbon fixation for burnt areas and the northward migration of boreal forest tree species may offset that release and maintain the current status of the Siberian Arctic as a C sink. Increased wildfire and loss of permafrost may threaten ongoing settlement and industrialization, particularly for western Siberia.